Nickel nanoparticles supported on a covalent triazine framework as electrocatalyst for oxygen evolution reaction and oxygen reduction reactions - Öztürk, Secil; Xiao, Yu-Xuan; Dietrich, Dennis; Giesen, Beatriz; Barthel, Juri; Ying, Jie; Yang, Xiao-Yu; Janiak, Christoph (Beilstein Journal of Nanotechnology, 2020)
Covalent triazine frameworks (CTFs) are little investigated, albeit they are promising candidates for electrocatalysis, especially for the oxygen evolution reaction (OER). In this work, nickel nanoparticles (from Ni(COD)2) were supported on CTF-1 materials, which were synthesized from 1,4-dicyanobenzene at 400 °C and 600 °C by the ionothermal method. CTF-1-600 and Ni/CTF-1-600 show high catalytic activity towards OER and a clear activity for the electrochemical oxygen reduction reaction (ORR). Ni/CTF-1-600 requires 374 mV overpotential in OER to reach 10 mA/cm2, which outperforms the benchmark RuO2 catalyst, which requires 403 mV under the same conditions. Ni/CTF-1-600 displays an OER catalytic activity comparable with many nickel-based electrocatalysts and is a potential candidate for OER. The same Ni/CTF-1-600 material shows a half-wave potential of 0.775 V for ORR, which is slightly lower than that of commercial Pt/C (0.890 V). Additionally, after accelerated durability tests of 2000 cycles, the material showed only a slight decrease in activity towards both OER and ORR, demonstrating its superior stability.
Keywords: covalent triazine framework (CTF); electrocatalysis; nickel nanoparticles; oxygen evolution reaction; oxygen reduction reaction

(untitled) - Lewis, N. S.; Nocera, D. G. (Proc. Natl. Acad. Sci. U. S. A., 2006)

(untitled) - Cook, T. R.; Dogutan, D. K.; Reece, S. Y.; Surendranath, Y.; Teets, T. S.; Nocera, D. G. (Chem. Rev., 2010)

(untitled) - Xu, H.; Ci, S.; Ding, Y.; Wang, G.; Wen, Z. (J. Mater. Chem. A, 2019)

(untitled) - Wang, Y.-J.; Zhao, N.; Fang, B.; Li, H.; Bi, X. T.; Wang, H. (Chem. Rev., 2015)

(untitled) - Lee, Y.; Suntivich, J.; May, K. J.; Perry, E. E.; Shao-Horn, Y. (J. Phys. Chem. Lett., 2012)

(untitled) - Deng, X.; Tüysüz, H. (ACS Catal., 2014)

(untitled) - Deng, X.; Öztürk, S.; Weidenthaler, C.; Tüysüz, H. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Song, F.; Hu, X. (J. Am. Chem. Soc., 2014)

(untitled) - Wu, G.; Zelenay, P. (Acc. Chem. Res., 2013)

(untitled) - Wu, G.; Santandreu, A.; Kellogg, W.; Gupta, S.; Ogoke, O.; Zhang, H.; Wang, H.-L.; Dai, L. (Nano Energy, 2016)

(untitled) - Osgood, H.; Devaguptapu, S. V.; Xu, H.; Cho, J.; Wu, G. (Nano Today, 2016)

(untitled) - Zhong, G.; Li, S.; Xu, S.; Liao, W.; Fu, X.; Peng, F. (ACS Sustainable Chem. Eng., 2018)

(untitled) - Wang, C.; Wang, Y.; Yang, H.; Zhang, Y.; Zhao, H.; Wang, Q. (Small, 2018)

(untitled) - Chen, S.; Duan, J.; Ran, J.; Jaroniec, M.; Qiao, S. Z. (Energy Environ. Sci., 2013)

(untitled) - Hoang, V. C.; Dinh, K. N.; Gomes, V. G. (Carbon, 2019)

(untitled) - Park, S.; Shao, Y.; Wan, H.; Rieke, P. C.; Viswanathan, V. V.; Towne, S. A.; Saraf, L. V.; Liu, J.; Lin, Y.; Wang, Y. (Electrochem. Commun., 2011)

(untitled) - Liu, Q.; Jin, J.; Zhang, J. (ACS Appl. Mater. Interfaces, 2013)

(untitled) - Liang, Y.; Wang, H.; Diao, P.; Chang, W.; Hong, G.; Li, Y.; Gong, M.; Xie, L.; Zhou, J.; Wang, J.; Reiger, T. Z.; Wie, F.; et al. (J. Am. Chem. Soc., 2012)

(untitled) - Chan-Thaw, C. E.; Villa, A.; Prati, L.; Thomas, A. (Chem. – Eur. J., 2011)

(untitled) - Chen, S.; Zhu, Y.; Xu, D.; Peng, W.; Li, Y.; Zhang, G.; Zhang, F.; Fan, X. (ChemElectroChem, 2018)

(untitled) - Kuhn, P.; Antonietti, M.; Thomas, A. (Angew. Chem., Int. Ed., 2008)

(untitled) - Kuhn, P.; Thomas, A.; Antonietti, M. (Macromolecules, 2009)

(untitled) - Siebels, M.; Schlüsener, C.; Thomas, J.; Xiao, Y.-X.; Yang, X.-Y.; Janiak, C. (J. Mater. Chem. A, 2019)

(untitled) - Katekomol, P.; Roeser, J.; Bojdys, M.; Weber, J.; Thomas, A. (Chem. Mater., 2013)

(untitled) - Wang, Z.; Liu, C.; Huang, Y.; Hu, Y.; Zhang, B. (Chem. Commun., 2016)

(untitled) - Lu, C.; Yang, J.; Wei, S.; Bi, S.; Xia, Y.; Chen, M.; Hou, Y.; Qiu, M.; Yuan, C.; Su, Y.; Zhang, F.; Liang, H.; et al. (Adv. Funct. Mater., 2019)

(untitled) - Zhang, Y.; Jin, S. (Polymers (Basel, Switz.), 2018)

(untitled) - Lan, X.; Du, C.; Cao, L.; She, T.; Li, Y.; Bai, G. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Bhunia, A.; Boldog, I.; Möller, A.; Janiak, C. (J. Mater. Chem. A, 2013)

(untitled) - Wang, K.; Yang, L.-M.; Wang, X.; Guo, L.; Cheng, G.; Zhang, C.; Jin, S.; Tan, B.; Cooper, A. (Angew. Chem., Int. Ed., 2017)

(untitled) - Ren, S.; Bojdys, M. J.; Dawson, R.; Laybourn, A.; Khimyak, Y. Z.; Adams, D. J.; Cooper, A. I. (Adv. Mater. (Weinheim, Ger.), 2012)

(untitled) - Kuhn, P.; Forget, A.; Su, D.; Thomas, A.; Antonietti, M. (J. Am. Chem. Soc., 2008)

(untitled) - Li, J.; Zhang, L.; Liu, X.; Shang, N.; Gao, S.; Feng, C.; Wang, C.; Wang, Z. (New J. Chem., 2018)

(untitled) - Su, P.; Iwase, K.; Harada, T.; Kamiya, K.; Nakanishi, S. (Chem. Sci., 2018)

(untitled) - Artz, J. (ChemCatChem, 2018)

(untitled) - Kamiya, K.; Kamai, R.; Hahimoto, K.; Nakanishi, S. (Nat. Commun., 2014)

(untitled) - Iwase, K.; Yoshioka, T.; Nakanishi, S.; Hashimoto, K.; Kamiya, K. (Angew. Chem., Int. Ed., 2015)

(untitled) - Gopi, S.; Kathiresan, M. (Polymer, 2017)

(untitled) - Yamaguchi, S.; Kamiya, K.; Hashimoto, K.; Nakanishi, S. (Chem. Commun., 2017)

(untitled) - Chan-Thaw, C. E.; Villa, A.; Katekomol, P.; Su, D.; Thomas, A.; Prati, L. (Nano Lett., 2010)

(untitled) - Li, Z.; He, T.; Liu, L.; Chen, W.; Zhang, M.; Wu, G.; Chen, P. (Chem. Sci., 2017)

(untitled) - Bhunia, A.; Dey, S.; Bous, M.; Zhang, C.; von Rybinski, W.; Janiak, C. (Chem. Commun., 2015)

(untitled) - Han, H.; Chao, S.; Yang, X.; Wang, X.; Wang, K.; Bai, Z.; Yang, L. (Int. J. Hydrogen Energy, 2017)

(untitled) - Zhang, X.; Xu, H.; Li, X.; Li, Y.; Yang, T.; Liang, Y. (ACS Catal., 2016)

(untitled) - Wegner, S.; Rutz, C.; Schütte, K.; Barthel, J.; Bushmelev, A.; Schmidt, A.; Dilchert, K.; Fischer, R. A.; Janiak, C. (Chem. – Eur. J., 2017)

(untitled) - Hao, L.; Zhang, S.; Liu, R.; Ning, J.; Zhang, G.; Zhi, L. (Adv. Mater. (Weinheim, Ger.), 2015)

(untitled) - Nassr, A. B. A. A.; Sinev, I.; Pohl, M.-M.; Grünert, W.; Bron, M. (ACS Catal., 2014)

(untitled) - Kundu, S.; Nagaiah, T. C.; Xia, W.; Wang, Y.; Van Dommele, S.; Bitter, J. H.; Santa, M.; Grundmeier, G.; Bron, M.; Schuhmann, W.; Muhler, M. (J. Phys. Chem. C, 2009)

(untitled) - Liu, G.; Li, X.; Ganesan, P.; Popov, B. N. (Appl. Catal., B, 2009)

(untitled) - Sun, J.; Wang, S.; Wang, Y.; Li, H.; Zhou, H.; Chen, B.; Zhang, X.; Chen, H.; Qu, K.; Zhao, J. (Catalysts, 2019)

(untitled) - Gong, M.; Dai, H. (Nano Res., 2015)

(untitled) - Zhu, K.; Wu, T.; Li, M.; Lu, R.; Zhu, X.; Yang, W. (J. Mater. Chem. A, 2017)

(untitled) - Dong, C.; Liu, X.; Wang, X.; Yuan, X.; Xu, Z.; Dong, W.; Riaz, M. S.; Li, G.; Huang, F. (J. Mater. Chem. A, 2017)

(untitled) - Xu, K.; Ding, H.; Lv, H.; Tao, S.; Chen, P.; Wu, X.; Chu, W.; Wu, C.; Xie, Y. (ACS Catal., 2017)

(untitled) - Cheng, N.; Liu, Q.; Tian, J.; Sun, X.; He, Y.; Zhai, S.; Asiri, A. M. (Int. J. Hydrogen Energy, 2015)

(untitled) - Stern, L.-A.; Hu, X. (Faraday Discuss., 2014)

(untitled) - Zhao, Y.; Nakamura, R.; Kamiya, K.; Nakanishi, S.; Hashimoto, K. (Nat. Commun., 2013)

(untitled) - Yuan, H.; Deng, L.; Cai, X.; Zhou, S.; Chen, Y.; Yuan, Y. (RSC Adv., 2015)

(untitled) - Tian, G.-L.; Zhao, M.-Q.; Yu, D.; Kong, X.-Y.; Huang, J.-Q.; Zhang, Q.; Wei, F. (Small, 2014)

(untitled) - Liu, Y.; Jiang, H.; Zhu, Y.; Yang, X.; Li, C. (J. Mater. Chem. A, 2016)

(untitled) - Zhu, J.; Xiao, M.; Zhang, Y.; Jin, Z.; Peng, Z.; Liu, C.; Chen, S.; Ge, J.; Xing, W. (ACS Catal., 2016)

(untitled) - Mao, J.; Liu, P.; Li, J.; Liang, D.; Yan, J.; Song, W. (Adv. Mater. Interfaces, 2019)

(untitled) - Huang, Z.-F.; Wang, J.; Peng, Y.; Jung, C.-Y.; Fisher, A.; Wang, X. (Adv. Energy Mater., 2017)

(untitled) - Farjami, E.; Rottmayer, M. A.; Jay Deiner, L. (J. Mater. Chem. A, 2013)

(untitled) - Kim, S.; Kato, S.; Ishizaki, T.; Li, O. L.; Kang, J. (Nanomaterials, 2019)

(untitled) - Kim, D.-w.; Li, O. L.; Pootawang, P.; Saito, N. (RSC Adv., 2014)

Ionic Liquids in Synthesis - Wasserscheid, P.; Welton, T. (Wiley-VCH, 2002)

(untitled) - Ernst Ruska-Centre for Microscopy and Spectroscopy with Electrons (J. Large-Scale Res. Facil., 2016)

(untitled) - Ernst Ruska-Centre for Microscopy and Spectroscopy with Electrons (J. Large-Scale Res. Facil., 2016)